Developing a machine learning model for predicting varicocelectomy outcomes: a pilot study - Coşkun Kaya; Mehmet Erhan Aydın; Özer Çelik; Aykut Aykaç; Mustafa Sungur (Journal of Men's Health)
A further debatable issue in the treatment of varicocele is which men would benefit from a varicocelectomy. Despite the increasing interest in Machine Learning (ML) in urology, there have been limited studies on the detection and prediction of varicocelectomy using artificial intelligence. We aimed to develop a model to predict the improvement in semen parameters after varicocelectomy using ML.The data for male patients who had clinical varicocele, abnormal semen parameters (low sperm concentration, reduced total motile sperm count, decreased progressive motility, and/or poor sperm morphology) and had received a varicocelectomy were recorded retrospectively. Demographic, anthropometric variables, physical examination findings, hematological, radiological, and semen analysis parameters were evaluated. The patients were separated into two groups according to the improvement in total motile sperm count postoperatively as improvement (Group 1) and no improvement (Group 2). The Extra Trees Classifier, Light Gradient Boosting Machine Classifier, eXtreme Gradient Boosting Classifier, Logistic Regression, and Random Forest Classifier techniques were used as ML algorithms.41 males were included in the study. 31 (75.6%) and 10 (24.4%) patients were classified as Group 1 and 2, respectively. The Extra Trees Classifier algorithm was found to be the best ML technique for predictions, according to the accuracy rates (92.3%) with an Area Under Curve of 0.92. We have shown for the first time in the literature that basic laboratory and semen analysis findings can be used to select patients who will benefit from varicocelectomy with the use of five ML methods. ML models could be identified as a new prediction tool for selecting the patients who will benefit from varicocelectomy. More detailed ML studies will be needed a larger number of patients.